Intravenous Administration of Carbetocin Versus Oxytocin for Preventing Postpartum Hemorrhage After Vaginal Delivery in High Risk Women: A Double-blind, Randomized Controlled Trial - Hua Liu; Xiu-Yun Xu; Ning Gu; Xiao-Dong Ye; Zhi-Qun Wang; Ya-Li Hu; Yi-Min Dai; Yan-Li Li; Yang Pan (Wolters Kluwer Health, 2020)
Abstract. Objective:. To compare the effects between carbetocin and oxytocin on reducing postpartum hemorrhage (PPH) after vaginal delivery in high risk pregnant women. Methods:. A prospective double-blinded randomized study was conducted in the Nanjing Drum Tower Hospital from March to May 2018. Women at or beyond 28 gestational weeks, cephalic presentation, 18-45 years old, and with at least one risk factor for PPH, were enrolled. Using a computer-generated randomization sequence, women were randomized to carbetocin group or oxytocin group which receive 100 μg intravenous infusion carbetocin or 10 IU intravenous infusion of oxytocin after anterior shoulder and before placental delivery. The primary outcome was the incidence of blood loss ≥500 mL within 24 hours postpartum. The secondary outcomes were amount of total blood loss, blood loss within 2 hours after delivery, the rate of blood loss ≥ 1 000 mL postpartum, need for a second-line uterotonics and interventions, blood transfusion, difference between hemoglobin before and 48 hours after delivery, adverse maternal events attributed to the trial medication. Hemodynamic status (blood pressure and pulse) was measured at 0 minutes, 30 minutes, 60 minutes, and 120 minutes after delivery. Results:. A total of 314 and 310 participants constituted the carbetocin and oxytocin groups, respectively. The baseline characteristics were comparable between the groups. The carbetocin group had similar rates of PPH (blood loss ≥500 mL) and rates of ≥1 000 mL PPH, (29.6% vs. 26.8%, P = 0.48) and (3.2% vs. 3.5%, P = 0.83), to the oxytocin group. The average amount of bleeding was (422.9 ± 241.4) mL in carbetocin group and (406.0 ± 257.5) mL in oxytocin group, which was no statistically significant difference (P = 0.40). Either the amount of blood loss within 2 hours ((55.5 ± 33.9) mL vs. (59.9 ± 48.7) mL) was no statistically significant difference (P = 0.19). The need for therapeutic uterotonics was 23.9% in carbetocin group and 23.5% in oxytocin group, which was also no statistically difference (P = 0.93). The rate of blood transfusion (P = 0.62) and hemoglobin change (P = 0.07) were not differ between the carbetocin and oxytocin groups. However, the rate of manually removing placenta was significantly different between two groups regarding the need for manually remove of placenta because of uterine bleeding in the third stage of labor (4 cases in carbetocin group vs. 13 cases in oxygen group), especially in those after oxytocin-induced or augmented labor (relative risk:3.39, 95% confidence interval: 1.09-10.52). After delivery, the blood pressure in the carbetocin group tend to be lower than that in the oxytocin group (P > 0.05), especially at 30 minutes postpartum (P < 0.05), while pulse tend to be simultaneously higher (P > 0.05). Conclusion:. Among women with high risk of PPH, intravenous carbetocin infusion did not better than oxytocin in the prevention of blood loss ≥500 mL after vaginal delivery.